Effect of Alkyd and Polyester Resin Compositions on Corrosion Resistance, Blistering, and Adhesion in utilization of Oily Sludge as Anti-rust Coating Material - Kakalang, Gerets Land; Kristianto, Yohanes David; Mudaryoto, Johny Wahyuadi (UI Scholars Hub, 2024)
Oil sludge is a waste derived from upstream and downstream activities of the oil and gas industry which is estimated at 10,000 tonnes generated from all PERTAMINA downstream activities spread across various fields, processing units and depots throughout Indonesia. Oil sludge has the same characteristics as asphalt, where asphalt in previous studies can be used as an anti-rust coating, so that the handling of oily sludge can be topped up by reusing and having its own added value. The purpose of this research is to utilise waste oily sludge as an alternative anti-rust coating material and compare alkyd resin and polyester resin on corrosion resistance, adhesion resistance, and pinhole characteristics of anti-rust coating materials. The method used in this research is that the oily sludge added to the forming ingredients for the coating, namely: CaCO3 (Calcium Carbonate), resin (polyester and alkyd), asphalt, wax and additives with a certain composition. The effect of adding 20 g resin will improve the corrosion resistance, blistering, and adhesion. Alkyd resins produce better corrosion and blistering resistance than polyester resins, where there is a 31% decrease in rust width for alkyd resins and 9% for polyester resins. As for adhesion, good results were obtained for both resins. In the pin holes test, pin holes were found to form in both resins. While in the atmospheric exposure test in the Tanjung Priok area, sample G1 was found to have undercutting while samples G5 and G6 formed alligatoring.